MODERN DIAGNOSTICS, CLINICAL PICTURE AND EPIDEMIOLOGY OF INTESTINAL YERSINIOSIS - Ostonova Gulruh Sodiqovna (World Scientific Research Journal, 2025)
Summary: Yersiniosis is a disease caused by several types of enteropathogenic Yersinia. They have an alimentary route of infection, clinically manifested by CNS intoxication, dyspepsia, tonsillitis, lymphadenopathy, rash, organ lesions in various organs. The survey data, as well as the diagnosis and treatment of 120 children aged 6 months to 14 years with acute diarrheal disease, were analyzed between 2021 and 2023, while they constituted the main study group, 40 children were examined for the control groups. All children under observation underwent extensive continuous examination, which included clinical and laboratory, biochemical, virological and immunological studies. In this regard, the emphasis was placed on their complaints, previous and concomitant diseases, the causes of the disease, the duration of the disease, the results of diagnostic and early treatment measures.